Food chemistry safety (CRC, 2002)
Provides those in the food industry with a comprehensive and authoritative survey of current developments in regulation, research, and best practice in the management of additives in food. Devotes a chapter to antioxidants and discusses preservatives, stabilizers, emulsifiers, and bulking agents.